Determination of Some Trace Elements in Air Samples from the Study Environment of Alasala National Colleges and Study of Irradiated Poly (Vinyl Alcohol) Film: Electrical Properties and Determination of Some Trace Elements - Aldagham, Hassan; Aljishi, Ahmad; Talag, Mustafa; Attia, Mohana (American Scientific Research Journal for Engineering, Technology, and Sciences, 2018)
This study included two objectives, firstly determination of some trace elements in air samples from the study environment of Alasala National Colleges and secondly study of Irradiated Poly (vinyl alcohol) Film: Electrical Properties and Determination of Some Trace Elements, in the same Environment. The investigate the level of trace elements including Lead [Pb], Copper [Cu], Zinc [Zn] in air samples collected from Alasala National Colleges in Dammam, KSA. The samples were analyzed by X-Ray Fluorescence (XRF). The enrichment factors relative to average soil and crustal rock were done of these trace elements to predict the possible sources of these elements in air. The study revealed that the analysis that is scholarly is wholly free from Pb. The ratio that is average of Zn is 0.0006 and Cu is 0.0003 ng/m3. Also the determination of some trace elements by thin film x-ray fluorescence and study of electrical properties of Poly (vinyl alcohol) using ion/electron beam. After preparing of the PVA films the trace elements are determined on thin-film samples by x-ray fluorescence spectrometry.  The limits of detection on the thin film are 0.05-0.7 ?g, depending on the element being measured. This study reports on the effect of nitrogen and electron beam irradiation on the electrical properties of ?lms. Films of 3 mm were exposed to a charged (ion/electron) beam for different treatment times; the beam was produced from a dual beam source using nitrogen gas with the other ion/electron source parameters optimized. The real () and imaginary ( ) parts of the dielectric constant decreased with frequency for all irradiated and non-irradiated samples.The AC conductivity showed an increase with frequency for all samples under the in?uence of both ion and electron irradiation for different times.